2013
DOI: 10.1371/journal.pone.0076973
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of the m2R-RGS6-IKACh Pathway in Controlling Intrinsic Heart Rate Variability

Abstract: Normal heart function requires generation of a regular rhythm by sinoatrial pacemaker cells and the alteration of this spontaneous heart rate by the autonomic input to match physiological demand. However, the molecular mechanisms that ensure consistent periodicity of cardiac contractions and fine tuning of this process by autonomic system are not completely understood.Here we examined the contribution of the m2R-IKACh intracellular signaling pathway, which mediates the negative chronotropic effect of parasympa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 44 publications
7
40
0
Order By: Relevance
“…Basal HR in hearts from Rgs6 Ϫ/Ϫ mice was significantly lower than measured in wild-type counterparts, consistent with published observations (14,16), whereas HR in hearts from Rgs4 Ϫ/Ϫ mice was normal ( Fig. 2A).…”
Section: Impact Of Rgs Ablationsupporting
confidence: 91%
See 4 more Smart Citations
“…Basal HR in hearts from Rgs6 Ϫ/Ϫ mice was significantly lower than measured in wild-type counterparts, consistent with published observations (14,16), whereas HR in hearts from Rgs4 Ϫ/Ϫ mice was normal ( Fig. 2A).…”
Section: Impact Of Rgs Ablationsupporting
confidence: 91%
“…3). Previous studies have shown that Girk4 gene ablation completely eliminates the whole-cell inward currents induced by CCh in SAN cells, confirming the I KACh dependence of the response (10,16). No significant genotype-dependent differences in peak or steady-state CCh-induced I KACh currents were observed in response to a saturating CCh concentration (10 M) (Fig.…”
Section: Rgs6supporting
confidence: 80%
See 3 more Smart Citations